Lending Growth, Non-Performing Loans and Loan Losses - Vera Kvisgaard; Bent Vale (Norges Bank, 2018)
At macro level, large loan losses for banks have often been preceded by periods of high lending growth. We analyse at bank level whether high loan growth also leads to more problem loans later on. The analysis is carried out on a panel of Norwegian banks covering the period 1996 - 2016. The applied methodology is similar to the one found in similar studies on Spanish banks as well as on banks in several OECD countries. We find a statistically significant positive relationship between past excessive loan growth at a bank and its amount of problem loans 2 - 3 years ahead. Unlike in the studies of other countries, the effect is not economically significant. Results do not indicate that excessive loan growth will never have any adverse effect at Norwegian banks, as our sample covers a relatively calm period in the Norwegian banking sector. Nevertheless, with a non-linear technique, we do find some indication that banks with much higher lending growth also experience proportionally much higher loan losses.
hdl:11250/2577274
Keywords: 330; lending growth; loan losses; dynamic panel model; spline model